Enhanced VEGF expression in hair follicle dermal papilla cells by Centella asiatica linn. - Pahol Saansoomchai (2018)
Centella asiatica Linn. (C. asiatica) extract has been shown to possess high antioxidant activity due to its phenols and flavonoids. This study tested the efficacy of 70%-ethanol (EtOH) crude extracts of C. asiatica and its fractions (H2O, EtOAc, CH2Cl2, and hexane) to modulate human follicle dermal papilla cells. In addition, we analyzed the extracts for major phytochemicals as well as free radical scavenging activity. Our results from ABTS and DPPH assays showed that the amounts of phenolic and flavonoid compounds in the extracts were both related to its free radical scavenging activity. While the EtOAc fraction of C. asiatica demonstrated the highest free radical scavenging activity, it was toxic to human follicle dermal papilla cells. The cell viability test was positive when cells were treated with EtOH crude extract and H2O fraction. VEGF gene expression, quantified by real-time PCR analysis of the EtOH crude extract, showed a significant level of induction, indicating that the growth promotion effect in human follicle dermal papilla cells was related to VEGF gene expression, which has a positive hair growth stimulating effect. The EtOH crude extract of C. asiatica may offer potential in hair growth promoting products.